Inhibiting Factors of Inventory Management: Study on Food and Beverage Micro Small And Medium Enterprises - Widyastuti, Widyastuti; Asandimitra, Nadia; Artanti, Yessy (International Review of Management and Marketing, 2018)
The production process in a business will run smoothly if the company has adequate raw material availability. Raw materials is one of the factors of production that management is quite complicated to do. The production process can not run smoothly if the available raw materials are not sufficient so that eventually the company will lose consumers. Conversely, an excess inventory of raw materials can increase storage costs, increasing the risk of damage so as to reduce the profit earned. For SMEs who produce food and beverages, managing raw material inventory is an important thing to do to get quality products so as to improve its performance. Raw materials used to make the production process is a raw material that is easy to rot and perishable. MSMEs are required to be able to produce quality products using fresh raw materials. This study aims to analyze the obstacles encountered by MSMEs in managing raw material inventory. Based on the results of the research can be seen that the availability of raw materials on the market, as well as unstable prices is a factor inhibiting MSMEs in doing raw material inventory. In addition, the storage of raw materials that still simple also become a constraint MSMEs to store raw materials in large quantities. Therefore, the government's role in stabilizing prices and supporting the availability of raw materials on the market. Keywords: inventory management, raw materials, inhibiting factors, perishable JEL Classifications : D2, D24, M1, M11